Pemberdayaan Masyarakat Melalui Edukasi Kesehatan Mental Dan Genitalia Guna Mencegah Parafilia Pada Anak Usia Dini - Nur Hidaayah; Khamida Khamida; Andikawati Fitriasari; Handayani Handayani; Francy Devy Octaviona (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Paraphilia is a mental disorder due to sexual deviation and free sex that can occur at all ages, can be dangerous regarding the sexuality of perpetrators and victims, so prevention is needed from an early age. Objective: to analyze the understanding of parents and the ability of PAUD mothers in preventing sexual deviations from children from an early age. Educational activities on the prevention of Sexual Deviance offline using leaflet media and direct observation of behavioral changes and environmental changes have been given to 16 parents and 4 PAUD mothers at PPT. Titian Ananda Karangrejo Surabaya. Results and discussion: After education through leaflets and videos between the FKK UNUSA community service team and parents, the team got feedback that there was a change in attitude through responses and statements from all parents and the behavior of all PAUD mothers on how to prevent sexual deviations in children when at home and at school. There is an increase in the understanding of early childhood parents and the ability to carry out independent education.